Design and optimization of a greener sinomenine hydrochloride preparation process considering variations among different batches of the medicinal herb - Ren, Dandan; Xie, Jiale; Chen, Tianle; Qu, Haibin; Gong, Xingchu (Chinese journal of chemical engineering, 2024)
The current methods used to industrially produce sinomenine hydrochloride involve several issues, including high solvent toxicity, long process flow, and low atomic utilization efficiency, and the greenness scores of the processes are below 65 points. To solve these problems, a new process using anisole as the extractant was proposed. Anisole exhibits high selectivity for sinomenine and can be connected to the subsequent water-washing steps. After alkalization of the medicinal material, heating extraction, water washing, and acidification crystallization were carried out. The process was modeled and optimized. The design space was constructed. The recommended operating ranges for the critical process parameters were 3.0–4.0 h for alkalization time, 60.0–80.0 °C for extraction temperature, 2.0–3.0 (volume ratio) for washing solution amount, and 2.0–2.4 mol·L−1 for hydrochloric acid concentration. The new process shows good robustness because different batches of medicinal materials did not greatly impact crystal purity or sinomenine transfer rate. The sinomenine transfer rate was about 20% higher than that of industrial processes. The greenness score increased to 90 points since the novel process proposed in this research solves the problems of long process flow, high solvent toxicity, and poor atomic economy, better aligning with the concept of green chemistry.